2017
DOI: 10.1016/j.bbagen.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

In silico investigation of lavandulyl flavonoids for the development of potent fatty acid synthase-inhibitory prototypes

Abstract: Background Inhibition of fatty acid synthase (FAS) is regarded as a sensible therapeutic strategy for the development of optimal anti-cancer agents. Flavonoids exhibit potent anti-neoplastic properties. Methods The MeOH extract of Sophora flavescens was subjected to chromatographic analyses such as VLC and HPLC for the purification of active flavonoids. The DP4 chemical-shift analysis protocol was employed to investigate the elusive chirality of the lavandulyl moiety of the purified polyphenols. Induced Fit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…As FASN is a lipid synthesis protein, it also plays an important role in obesity (Oh et al, 2017; Tan et al, 2019). Orlistat, an anti‐obesity drug is also proven to be an effective FASN inhibitor (Pemble et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As FASN is a lipid synthesis protein, it also plays an important role in obesity (Oh et al, 2017; Tan et al, 2019). Orlistat, an anti‐obesity drug is also proven to be an effective FASN inhibitor (Pemble et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen bonding is observed between C‐4 carbonyl oxygen and sulphonyl hydrogen of Cys161, 7‐OH and carbonyl oxygen of Ser 265 and carboxylate oxygen of Asp254. The negative vander waal interactions with hydrophobic amino acid residues and hydrogen bonding highly enhance the binding affinity in the KS domain (Oh et al, 2017). Luteolin ( 13 ), a flavonoid present in celery, thyme, green peppers, chamomile tea, etc., has a structure that resembles P13K inhibitor showing an IC 50 value of 2.5 µg/ml against FASN.…”
Section: Natural Compounds As Inhibitors Of Fasnmentioning
confidence: 99%
“…Pancreatic lipase belongs to the lipase superfamily, similar to LPL, and has been reported to be directly regulated by polyphenols . For example, previous studies have shown that polyphenols derived from berry and tea elicit anti-lipase activity, , and this finding was further supported by Sergent et al Previous studies have also suggested that polyphenols alter lipid metabolism via multiple mechanisms, including decreased levels of cholesterol and fatty acid synthesis and reduced production of reactive oxygen species (ROS), consequently leading to decreased risks of CVD. However, few studies have examined the effect of polyphenols on LPL activity.…”
Section: Introductionmentioning
confidence: 90%
“…Concerning the KS domain, several inhibitors have been reported in the literature . For examples, inhibitors of the KS domain are structurally related to flavonoids such as morin and luteolin . Other described KS inhibitors are the thiolactone thiolactomycin, the epoxyde cerulenin, the lactone C75 or are related to hydroxyquinolinone or isochromanone derivatives (Scheme ).…”
Section: Introductionmentioning
confidence: 99%